Evaluation of Dermatoglyphic Features of Type 2 Diabetic Patients as Compared to Non-Diabetics Attending Hospitals in Southern Ethiopia - Tadesse A; Gebremickael A; Merid M; Wondmagegn H; Melaku T; Ayele T; Meskele S; Esubalew H; Birhanu A (Diabetes, Metabolic Syndrome and Obesity, 2022)
Amanuel Tadesse,1 Abinet Gebremickael,2 Melkamu Merid,3 Habtamu Wondmagegn,2 Tesfaye Melaku,1 Tsegazeab Ayele,2 Simeon Meskele,1 Habtamu Esubalew,3 Asaminew Birhanu2 1Department of Human Anatomy, College of Medicine and Health Sciences, Dilla University, Dilla, Ethiopia; 2Department of Human Anatomy, College of Medicine and Health Sciences, Arba Minch University, Arba Minch, Ethiopia; 3Department of Public Health, College of Medicine and Health Sciences, Arba Minch University, Arba Minch, EthiopiaCorrespondence: Habtamu Wondmagegn, Department of Human Anatomy, College of Medicine and Health Sciences, Arba Minch University, Post Box No: 21, Arba Minch, Ethiopia, Tel +251 913028959, Fax +251 0468810279, Email habtamuwondmagegn@gmail.com; habtamu.wondmagegn@amu.edu.etBackground: Diabetes mellitus (DM) is a complex metabolic disorder characterized by persistent hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Type 2 DM has a strong hereditary background. A study of the dermatoglyphic features can help in the early identification of people with a genetic predisposition to develop type 2 DM.Purpose of the Study: The study was aimed to compare the finger and palmar dermatoglyphics features in type 2 diabetic and non-diabetic patients and to evaluate the association with other variables.Patients and Materials: Institution-based cross-sectional study was conducted in one referral hospital and three primary hospitals located in Gedeo Zone. Three hundred ninety study participants (130 type 2 diabetics and 260 non-diabetics) from adult OPD and diabetic clinics were included in the study. The association among different dermatoglyphics variables was analyzed using the chi-square test. An independent t-test was conducted to analyze the mean difference and to test the significance of numerical variables. A statistically significant association was declared at P-value < 0.05.Results: In the present study, a total of 3900 digits (1300 from type 2 diabetic and 2600 non-diabetic) were analyzed for distribution of digital dermatoglyphic patterns. Loop pattern is found to be the commonest in both study groups with a prevalence of 65.8% and 60.7% among type 2 diabetics and non-diabetics, respectively. Both the right-left axial tri-radius angle was significantly higher in type 2 diabetes mellitus patients compared to non-diabetic study participants. Total finger ridge counts and absolute finger ridge counts showed no significant difference in both groups.Conclusion: The study revealed Loop pattern was more frequent in type 2 DM compared to non-diabetic study participants. Whorl type was more common than arch type in non-diabetic patients compared to type 2 DM groups. The result also showed tri-radius angle is significantly wider in diabetic groups in both hands.Keywords: dermatoglyphics, type 2 DM, dermatoglyphic patterns, Gedeo Zone